Secreted phosphoprotein 1 as a potential prognostic and immunotherapy biomarker in multiple human cancers. Issue 2 (1st February 2022) - Zeng, Ping; Zhang, Xujun; Xiang, Tianxin; Ling, Zongxin; Lin, Chenhong; Diao, Hongyan
ABSTRACT: Secreted phosphoprotein 1 ( SPP1 ) is involved in immune regulation, cell survival, and tumor progression. Studies have demonstrated that SPP1 plays an important role in certain individual tumors. However, the expression profile and oncogenic features of SPP1 in diverse cancers are remaining unknown. Therefore, we performed a comprehensive analysis using The Cancer Genome Atlas (TCGA) database. Raw data of 33 cancer types were download from the University of California Santa Cruz (UCSC) Xena website. The expression of SPP1 and its relationship with tumor prognosis, immune invasion, tumor microenvironment, and immunotherapy were analyzed using the R language. The function analysis was conducted using Gene Set Enrichment Analysis (GSEA). The oncogenic features of SPP1 was validated by wound-healing assay and EdU staining assay. SPP1 highly expressed in most cancers. The expression of SPP1 was significant related to prognosis, tumor mutation burden (TMB), microsatellite instability (MSI), and immune checkpoint genes, suggested that SPP1 plays an essential role in the tumor immune microenvironment and immune cell infiltration. The immune/stromal scores correlated positively with the SPP1 expression, and the relationship was affected by tumor heterogeneity and immunotherapy. In addition, SPP1 could predict the response of tumor immunotherapy. Functional analysis revealed the SPP1 -associated terms and pathways. Finally, SPP1 significantly elevated cell proliferation and migration in A549, Huh7, HT-29, A2780 tumor cell lines. In conclusion, this study indicated that SPP1 involved in tumorigenesis, tumor progression, and regulated tumor immune microenvironment, revealing SPP1 might be a potential target for evaluating prognosis and immunotherapy in multiple cancers.